2019
DOI: 10.1111/anec.12637
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic measures of ventricular repolarization dispersion and arrhythmic outcomes among ST elevation myocardial infarction patients with pre‐infarction angina undergoing primary percutaneous coronary intervention

Abstract: Background: Arrhythmias are considered one of the major causes of death in ST elevation myocardial infarction (STEMI), particularly in the early in-hospital phase. Preinfarction angina (PIA) has been suggested to have a protective role. Objectives:To study the difference in acute electrocardiographic findings between STEMI patients with and without PIA and to assess the in-hospital arrhythmias in both groups. Material and Methods: We prospectively enrolled 238 consecutive patients with STEMI. Patients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…An analysis according to preinfarction angina (PIA) was conducted and revealed that STEMI patients with PIA had a lower chance of suffering from VA than those without PIA–who had longer Tp-e, Tp-e/QT ratio, which independently predicted in-hospital VA [ 98 ]. Interestingly, Tp-e was found to predict Intensive Care Unit (ICU) stay among patients with acute coronary syndrome (ACS) with COVID-19 [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis according to preinfarction angina (PIA) was conducted and revealed that STEMI patients with PIA had a lower chance of suffering from VA than those without PIA–who had longer Tp-e, Tp-e/QT ratio, which independently predicted in-hospital VA [ 98 ]. Interestingly, Tp-e was found to predict Intensive Care Unit (ICU) stay among patients with acute coronary syndrome (ACS) with COVID-19 [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Elderly patients are more likely to ignore their symptoms [ 19 ]. Research shows that compared to patients without pain, not only thrombolytic treatment, patients with pre-infarction angina (PIA) have better in-hospital outcomes after PCI treatment [ 20 ]. Our study suggests that persistent chest tightness/pain is a protective factor of S2FMC, as continuous discomfort can attract patients’ attention and thereby shorten the S2FMC.…”
Section: Discussionmentioning
confidence: 99%
“…PCI: percutaneous coronary intervention, STEMI: ST-elevation myocardial infarction, PIA: postinfarction angina, QTd: QT dispersion, QTc: corrected QT, STR: ST-segment resolution, Tp-Te: T-peak-to-T-end interval, PTCA: percutaneous transluminal coronary angioplasty, HRV: heart rate variability, AMI: acute myocardial infarction, TPE: T-wave peak to end, CABG: coronary artery bypass graft, SK: streptokinase[19][20][21][22][23][24][25][26][27][28][29][30] …”
mentioning
confidence: 99%